The war in Ukraine as an opportunity to teach critical thinking (Journal of Applied Learning and Teaching, 2022)
Although the war in Ukraine is the most extensively documented conflict ever, it is difficult to discern what is real, fictitious or from a state misinformation campaign. In the battle of spinning media narratives, the truth easily becomes a casualty. We explore the war in the context of various historical key events and reject a possible application of Baudrillard’s perspective that ‘there was no Gulf war’ to the current conflict. We note the eerie resemblance of Russian media fabrications with the Nazis’ big lie technique. The enormous toll of the war on Ukraine and the world is clearly stated. The war in Ukraine and the battle over the accuracy and legitimacy of history, knowledge and reality remind us of the crucial importance of teaching critical thinking. Critical thinking helps us see through manipulative and politically distortive usages of language to suit ideological purposes. In using the war in Ukraine as an opportunity to teach critical thinking, we can follow a generic model of gradual sequencing that prominently features modelling and scaffolding. In an era of weaponised lies and alternative facts, critical thinking has a central role in education, from kindergarten to university, with the purpose of education being the creation of an informed citizenry. Although critical thinking – and teaching critical thinking – are challenging, it is when both teachers and students realise their own responsibilities for creating a learning community that learning is at its most useful and critical thinking becomes empowering.